2018
DOI: 10.1186/s40463-018-0317-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of discovery learning using a mobile otoscopy simulator on knowledge acquisition and retention in medical students: a randomized controlled trial

Abstract: BackgroundPortable educational technologies, like simulators, afford students the opportunity to learn independently. A key question in education, is how to pair self-regulated learning (SRL) with direct instruction. A cloud-based portable otoscopy simulator was employed to compare two curricula involving SRL. Pre-clerkship medical students used a prototype smartphone application, a 3D ear attachment and an otoscope to complete either otoscopy curriculum.MethodsPre-clerkship medical students were recruited and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
0
13
1
Order By: Relevance
“…Smartphones have brought massive changes to people's lives, allowing, in the case of students, easy access to information, diverse social communications and learning possibilities [45]. Portable educational technologies, such as simulators, provide students with the opportunity to learn independently [48]. As we have highlighted above, given that students use and carry their smartphones every day, and their behaviors are reflected in their smartphone use, it is important to explore ways to support self-regulation through smartphones [45].…”
Section: Smartphones As Ubiquitous Supports For Self-regulation Of Le...mentioning
confidence: 99%
“…Smartphones have brought massive changes to people's lives, allowing, in the case of students, easy access to information, diverse social communications and learning possibilities [45]. Portable educational technologies, such as simulators, provide students with the opportunity to learn independently [48]. As we have highlighted above, given that students use and carry their smartphones every day, and their behaviors are reflected in their smartphone use, it is important to explore ways to support self-regulation through smartphones [45].…”
Section: Smartphones As Ubiquitous Supports For Self-regulation Of Le...mentioning
confidence: 99%
“…Given that smartphone, tablet, or computer apps are easily accessible and everyday tools, especially by students (Kortabitarte et al, 2018;Hartley et al, 2020), studies have identified that using smartphones in the service of learning generates positive academic outcomes (Anshari et al, 2017;Nguyen et al, 2018;Ariel and Elishar-Malka, 2019;Dalvi-Esfahani et al, 2020) and that using them for non-academic purposes (e.g., to check virtual social networks) burdens students' cognitive resource management by being a source of distraction when studying and when performing academic tasks outside of class (May and Elder, 2018;Aharony and Zion, 2019), which is associated with lower academic performance (Lepp et al, 2015;Chen and Yan, 2016). A small, recent body of research evaluates the impact of asking students to self-regulate their learning using apps (Xu et al, 2018;Foerst et al, 2019;Hendikawati et al, 2019;Kim et al, 2019;Loeffler et al, 2019;Broadbent et al, 2020;Hartley et al, 2020). Lobos et al (2021a) used the self-regulation of learning model proposed by Zimmerman (2002) to design the 4Planning app for smartphone, with the aim of evaluating its impact on the SRL of 473 1st-year engineering students in face-to-face mode, belonging to seven Chilean universities, during the first semester of 2019.…”
Section: Introductionmentioning
confidence: 99%
“…As part of their research, Lobos et al (2021a) systematically reviewed interventions that promoted SRL in college students using smartphones. While the seven studies they identified consider academic performance in argumentation, only two incorporated it as a dependent variable in their models (Xu et al, 2018;Hartley et al, 2020), but the proposed interventions did not generate a statistically significant impact. In addition, there is only one study of the effect of the 4Planning app on SRL, in a sample of engineering students, in face-to-face modality, without pandemic, and also did not consider performance as a dependent variable (Lobos et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…One main goal of medical education is to fulfil the educational needs of the student. We conclude that students should be trained in their preferred examination methods to achieve the highest levels of confidence and skill, especially in the age of self-regulated learning and student-centered medical education [ 19 ]. We thus propose taking into consideration the students’ own support for teaching endoscopic ear examination in the future.…”
Section: Discussionmentioning
confidence: 99%